A Multimodal Discourse Analysis of the Notion of Beauty in “Dove Real Beauty Sketches” - Janice Davita Oey (Kata Kita: Journal of Language, Literature, and Teaching, 2019)
This research deals with multimodality or multimodal discourse analysis in analyzing the notion of beauty in a Youtube video. It aims at finding how an advertisement uses the multiple modes in constructing the meaning, which is the notion of beauty. For this research, the object of the analysis is Dove’s video advertisement entitled “Dove Real Beauty Sketches”, which was uploaded to the YouTube channel of Dove in 2013. The issue that Dove is trying to convey through the advertisement is that beauty is in the eye of the beholder. One’s perception of beauty can differ from another. If one person describe himself/herself as unattractive, other people may think that the person is actually attractive. Through this research, I want to find how that issue is constructed through the analysis of the multiple modes used in the advertisement. The multiple modes consist of the verbal and non-verbal expressions displayed by the female participants, Olivia, Melinda, Kela, and Florence. Keywords: advertisement, beauty, notion, multimodal discourse analysis